Visualisasi Perempuan Dalam Perspektif AL-Qur’an: Antara Teks dan Konteks - Aziz, Abdul (Analisis: Jurnal Studi Keislaman, 2017)
One of the missions in Al-Qur'an is to uphold justice between men and women. But the justice and equality mission that is in the Qur'an which is "wrapped up" in the statements of the verse, does not always literally show equality between men and women. Rather, it is the opposite that explicitly puts men in a superior position compared to women. The implicit statement and message of justice contained in the verses of the Qur'an also fades with the existence of classical interpretations that seem to prioritize men. Is there a mistake in the text or in how to understand it. This article aims to discuss how the provisions of the role of women in the Islamic view? The results of this study found that although normatively, the Qur'an and al-Hadith formulated several signs that must be obeyed by women, but that was undoubtedly perceived in a whole. Women in their role as social beings to be able to produce in the public, social and political realm. In this case Islam has regulated it, there is no limit that limits it if the woman has the ability to jump into the public domain, with a note that she is still paying attention to the syar'i signs that have been determined by Allah.